2022
DOI: 10.3389/fmed.2021.785744
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Activity in Anti-TNF-Treated Rheumatoid Arthritis and Ankylosing Spondylitis Patients

Abstract: IntroductionAngiotensin-converting enzyme (ACE) and ACE2 have been implicated in the regulation of vascular physiology. Elevated synovial and decreased or normal ACE or ACE2 levels have been found in rheumatoid arthritis (RA). Very little is known about the effects of tumor necrosis factor α (TNF-α) inhibition on ACE or ACE2 homeostasis. In this study, we assessed the effects of one-year anti-TNF therapy on ACE and ACE2 production in RA and ankylosing spondylitis (AS) in association with other biomarkers.Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Coagulation screening tests (prothrombin time, activated partial thromboplastin time, thrombin time) and fibrinogen were measured by routine methods (Siemens Healthcare Diagnostic Products, Marburg, Germany). ACE and ACE2 activities were assessed using specific quenched fluorescent substrates as described earlier ( 5 , 6 ). Anti-SARS-CoV-2 rapid antigen test was carried out in the patient and controls from nasopharyngeal swab samples (Genedia, St. Ingbert, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Coagulation screening tests (prothrombin time, activated partial thromboplastin time, thrombin time) and fibrinogen were measured by routine methods (Siemens Healthcare Diagnostic Products, Marburg, Germany). ACE and ACE2 activities were assessed using specific quenched fluorescent substrates as described earlier ( 5 , 6 ). Anti-SARS-CoV-2 rapid antigen test was carried out in the patient and controls from nasopharyngeal swab samples (Genedia, St. Ingbert, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Fibrinogen levels were measured according to the method of Clauss on a BCS coagulometer (Siemens Healthcare Diagnostic Products, Marburg, Germany). Serum angiotensin convertase enzyme 2 (ACE2) activity was assessed using a specific quenched fluorescent substrate as described earlier ( 17 ). For the execution of thrombin generation assay, aliquots of citrated plasma were stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Serum ACE levels were determined by a commercial human ACE ELISA (R&D Systems) as described previously ( 15 , 29 ). ELISA plates (Greiner Bio-One) were coated with 80 ng/well capture antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that anti-TNF agents increased ACE and ACE2 levels, as well as the ACE/ACE2 ratio in RA patients. We correlated ACE and ACE2 levels with disease duration, C-reactive protein (CRP), rheumatoid factor (RF), FMD and ccIMT ( 29 ).…”
Section: Introductionmentioning
confidence: 99%